1997
DOI: 10.1007/s11664-997-0111-y
|View full text |Cite
|
Sign up to set email alerts
|

InxGa1−xAs ohmic contacts to n-type GaAs with a tungsten nitride barrier

Abstract: Significant reduction of the contact resistance of In0.TGaoaAs/Ni/W contacts (which were previously developed by sputtering in our laboratory) was achieved by depositing a W2N barrier layer between the Ni layer and W layer. The In07Gao.sAs/Ni/W2N/W contact prepared by the radio-frequency sputtering technique showed the lowest contact resistance of 0.2 ~mm after annealing at 550~ for 10 s. This contact also provided a smooth surface, good reproducibility, and excellent thermal stability at 400~ The polycrystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(3 reference statements)
1
9
0
Order By: Relevance
“…1. 4 Isothermal annealing at 400°C after contact formation was performed for the contact which was deposited on the GaAs substrate etched at a depth of 100 nm and annealed at 550°C for 10 s. The R c values are constant for 5 h and slightly increase after annealing for 10 h as shown in Fig. The diffusion depth of the contact metals after annealing at 550°C for 10 s was measured to be about 50 nm.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…1. 4 Isothermal annealing at 400°C after contact formation was performed for the contact which was deposited on the GaAs substrate etched at a depth of 100 nm and annealed at 550°C for 10 s. The R c values are constant for 5 h and slightly increase after annealing for 10 h as shown in Fig. The diffusion depth of the contact metals after annealing at 550°C for 10 s was measured to be about 50 nm.…”
Section: Discussionmentioning
confidence: 98%
“…4 The measured R c values are plotted by a solid curve in Fig. These samples were prepared by annealing at 550°C for 10 s (note that this annealing condition provided the lowest R c value for n-type GaAs).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Recently, thermally stable, low resistance InGaAs/Ni/W 2 N/W ohmic contact to n-GaAs was also developed by forming the intermediate In x Ga 1-x As layer. 9 We have previously explored a possibility to reduce the SBH by forming an intermediate layer at p-ZnSe/metal interface and found that Cd reacted with ZnSe after annealing at temperatures higher than 250°C, forming a Cd-rich Cd x Zn 1-x Se (x≥0.9) layer epitaxially grown on the ZnSe. 10,11 However, no ohmic J-V behavior was obtained.…”
Section: Introductionmentioning
confidence: 99%